Study of different curcumins for staphylococcus aureus antimicrobial photodynamic therapy - Joshi, Priyankaben Niravkumar (2023)
Curcumin is a Photosensitizer (PS) used for microbial inactivation when light is applied. Antimicrobial photodynamic therapy (aPDT) is a promising approach for treatment of bacterial infections, combining a PS + light to produce reactive species of oxygen that kills the microorganisms. This project aims to analyze the effectiveness of different in vitro curcumin formulations for PDT protocol against S.aureus. In this study, we compared Synthetic curcumin (Cur-Syn) with Nanoencapsulated Curcumin (Cur-Nano), as well as curcumins modified with Chlorine (Cl), Selenium (Se), and Iodine(I) (Cur-Cl, Cur-Se, Cur-I). Staphylococcus aureus (ATCC 25923) was incubated with Curcumin and irradiated at 450nm to evaluate the effects of aPDT. Mortality was measured by counting the surviving colony forming units per milliliter (CFU/ml). The Uptake of photosensitizer (PS) and photobleaching were compared for the curcumins of interest. Our in vitro results suggest that Nanoencapsulated curcumin wasn't able to release curcumin and attack the bacteria when compared with Cur-Syn in the same conditions. Also, of the three modifications of Cur-Cl, Cur-Se, Cur-I; Cur-Se, had detrimental effect on bacteria. However, the rate of uptake and photobleaching capacity of Cur-Syn and Cur-Se were found to be quite similar. Our results suggest that curcumin modifications influence the effect of the molecule on PS.